Application of Squishy Intervention With Combination Active ROM To Increase Muscle Strength Hands On Stroke Patient - Irgi Biantara; Arif Wahyu Setyo Budi; Nurchayati Nurchayati; Puspitowarno Puspitowarno; Fitnaningsih Endang Cahyawati (Lembaga Pengembangan Kinerja Dosen, 2023)
Introduction– Stroke is a non-communicable disease that has an impact on the loss of motor skills in the extremities. One intervention that can overcome this problem is the application of squishy with a combination of active ROM. Purpose– The purpose of this case study was to conduct nursing care on the application of squishy intervention to increase hand muscle strength in stroke patients. Methodology/Approach – The method used in writing is a case report which was carried out for 6 days with Active ROM combination squishy intervention. Findings– The results of this scientific work show that with the active ROM combination squishy intervention for 6 days, there is a significant increase in muscle strength in the right upper extremity before the intervention is worth 2 and after the intervention is worth 4. Conclusion– The effectiveness of the application of nursing care standards in increasing muscle strength given to patients shows a change in muscle strength on the third day to the fifth day with a muscle strength value of 3 and the sixth day with a muscle strength value of 4.